2014
DOI: 10.1152/japplphysiol.01123.2013
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction in chronic thromboembolic obstruction of the pulmonary artery: a pressure-volume study using the conductance catheter

Abstract: Pressure-volume loops describe dynamic ventricular performance, relevant to patients with and at risk of pulmonary hypertension. We used conductance catheter-derived pressure-volume loops to measure right ventricular (RV) mechanics in patients with chronic thromboembolic pulmonary arterial obstruction at different stages of pathological adaptation. Resting conductance catheterization was performed in 24 patients: 10 with chronic thromboembolic pulmonary hypertension (CTEPH), 7 with chronic thromboembolic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 35 publications
1
80
1
Order By: Relevance
“…This study demonstrated that CTED patients have impaired right ventricular adaptation to exercise and inefficient gas exchange on exertion [26]. Moreover, our study on right ventricular mechanics using conductance catheter derived pressure-volume loops showed delayed right ventricular relaxation in these patients [27].…”
Section: Discussionmentioning
confidence: 49%
“…This study demonstrated that CTED patients have impaired right ventricular adaptation to exercise and inefficient gas exchange on exertion [26]. Moreover, our study on right ventricular mechanics using conductance catheter derived pressure-volume loops showed delayed right ventricular relaxation in these patients [27].…”
Section: Discussionmentioning
confidence: 49%
“…Most recently, high-fidelity RV pressure and volume measurements, and single-beat Emax calculations have been reported in a small series of patients with chronic thromboembolic pulmonary hypertension (CTEPH), a condition with similar symptomatology to that of PAH [21]. This limited size report confirms the importance of systolic function adaptation with an increased Emax to maintain RV-arterial coupling in the face of severe increases in PAP, in agreement with previous studies in various animal species [10].…”
Section: Systolic Function Of the Right Ventriclementioning
confidence: 99%
“…In addition, following an episode of acute pulmonary emboli a growing number of patients are being identified with persistent dyspnoea in the absence of pulmonary hypertension (mean pulmonary arterial pressure ,25 mmHg at rest), affecting their exercise capacity and quality of life [16]. The symptoms of breathlessness in these patients can be related to excessive dead space ventilation, pulmonary hypertension on exercise and/or maladaptation of the right ventricle to the decreased pulmonary artery compliance [17,18]. The prognosis and risk of progression to a more severe form of pulmonary hypertension, however, remains unclear.…”
mentioning
confidence: 99%